2011
DOI: 10.1074/jbc.m110.195370
|View full text |Cite
|
Sign up to set email alerts
|

BH3-only Activator Proteins Bid and Bim Are Dispensable for Bak/Bax-dependent Thrombocyte Apoptosis Induced by Bcl-xL Deficiency

Abstract: A pivotal step in the mitochondrial pathway of apoptosis is activation of Bak and Bax, although the molecular mechanism remains controversial. To examine whether mitochondrial apoptosis can be induced by just a lack of antiapoptotic Bcl-2-like proteins or requires direct activators of the BH3-only proteins including Bid and Bim, we studied the molecular requisites for platelet apoptosis induced by Bcl-xL deficiency. Severe thrombocytopenia induced by thrombocyte-specific Bcl-xL knock-out was fully rescued in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 44 publications
11
70
0
Order By: Relevance
“…We used previously generated megakaryocytic lineage-specific homozygote Bcl-xL knockout mice (bcl-x flox/flox pf4-cre), 15 which presented with severe thrombocytopenia due to massive platelet apoptosis. 11,12 As previously reported, despite severe thrombocytopenia, Bcl-xL knockout mice were born at the expected Mendelian frequency and did not show any gross abnormality; 15 analysis at embryonic day (ED) 13.5 also revealed that Bcl-xL knockout embryos grew up normally at the expected Mendelian frequency (Supplementary Table 1). We confirmed that Bcl-xL expression was efficiently diminished in the cultured megakaryocytes of the knockout mice ( Figure 1j) as well as in the platelets.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…We used previously generated megakaryocytic lineage-specific homozygote Bcl-xL knockout mice (bcl-x flox/flox pf4-cre), 15 which presented with severe thrombocytopenia due to massive platelet apoptosis. 11,12 As previously reported, despite severe thrombocytopenia, Bcl-xL knockout mice were born at the expected Mendelian frequency and did not show any gross abnormality; 15 analysis at embryonic day (ED) 13.5 also revealed that Bcl-xL knockout embryos grew up normally at the expected Mendelian frequency (Supplementary Table 1). We confirmed that Bcl-xL expression was efficiently diminished in the cultured megakaryocytes of the knockout mice ( Figure 1j) as well as in the platelets.…”
Section: Resultsmentioning
confidence: 52%
“…It should be noted that Bak deficiency caused modest thrombocytosis due to the prolonged lifespan of their platelets. 11,12 Mature megakaryocyte and platelet counts of the quadruple knockout mice were not significantly different from the control Bak knockout littermates (Figures 3b-d). The TUNEL-positive cell ratio of mature megakaryocytes in the quadruple knockout mice was very low and not different from their littermates (Figure 3e), suggesting that mature megakaryocyte apoptosis in the absence of both Bcl-xL and Mcl-1 could be prevented in a Bak and Bax knockout background.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Interestingly, lowering levels of pro-survival Bcl-2 family members alone can lead to apoptosis. 8 Necroptotic cell death is also dependent on BAX 9 and observed in injured neurons, but may not require BIM, BBC3, and BID. Finally, it is possible that BAX activation could be occurring independently of the Bcl-2 family (e.g.…”
mentioning
confidence: 99%